PEMBELAJARAN BERBASIS PROYEK PADA KURIKULUM MERDEKA DALAM MENINGKATKAN MOTIVASI DAN KEMANDIRIAN SISWA DI ERA SOCIETY 5.0 - Khasanah, Taufiqoh; Trinindita Nayla Nabilla; Farah Dilah Zahra; Brilian Galang Irzaqi; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Project Based Learning (PjBL) is a learning model that aligns with the principles of the Merdeka Curriculum by placing students at the center of the learning process while promoting the development of 21st-century skills. This study aims to examine the role of Project Based Learning in enhancing students' learning motivation and learning independence, as well as its relevance to the implementation of the Merdeka Curriculum in the Society 5.0 era. This research employed a library research method using a descriptive qualitative approach. The data were collected from 26 scientific articles published between 2021 and 2025, obtained through the Google Scholar and Garuda databases. The data were analyzed using content analysis to identify research findings related to the implementation of PjBL, learning motivation, and learning independence. The findings indicate that Project Based Learning enhances students' learning motivation by actively engaging them in project completion, fostering self-confidence, and improving collaboration and communication skills. Furthermore, PjBL contributes to the development of learning independence by encouraging students to plan, implement, and evaluate their own learning processes. These findings demonstrate that Project Based Learning is an effective instructional model for supporting the implementation of the Merdeka Curriculum while preparing students with the competencies required to face the challenges of the Society 5.0 era.